2011
DOI: 10.4161/psb.6.7.15580
|View full text |Cite
|
Sign up to set email alerts
|

AGC kinases in plant development and defense

Abstract: PDK1 Activates AGC KinasesIn mammalian systems, most of the cellular responses to phosphatidylinositol-3-kinase activation and phosphatidylinositol-3,4,5-trisphosphate production are mediated by the activation of a subgroup of Ser/Thr protein kinases termed AGC (cAMP-dependent protein kinase A/cGMP-dependent protein kinase G/protein kinase C), which play essential roles in cell growth, proliferation, survival, metabolism and apoptosis.1 Many AGC kinases possess a common upstream activator, namely PDK1 (3-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…In addition, we identified the phosphoinositide‐specific phospholipase C, PLC2, as a putative target of AGC kinases. PLCs generate diacylglycerol that activates PKCs in animals and is rapidly phosphorylated into phosphatidic acid in plants, leading to the activation of AGC kinases . Of potential relevance in such pathway is AT4G32285, a protein active in phosphatidylinositol binding that might be phosphorylated by AGC kinases as well (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified the phosphoinositide‐specific phospholipase C, PLC2, as a putative target of AGC kinases. PLCs generate diacylglycerol that activates PKCs in animals and is rapidly phosphorylated into phosphatidic acid in plants, leading to the activation of AGC kinases . Of potential relevance in such pathway is AT4G32285, a protein active in phosphatidylinositol binding that might be phosphorylated by AGC kinases as well (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This attracts many researchers to use the positive effects of P. indica as a model system to study the molecular basis of mutualistic symbioses and symbiont-induced plant immunity (Qiang et al , 2012). Genetic and biochemical analyses uncovered possible signal transduction processes induced by P. indica in the root cells of host plants (Shahollari et al , 2005, 2007; Serfling et al , 2007; Vadassery et al , 2009 b ; Camehl et al , 2011; Hirt et al , 2011; Lee et al , 2011). Furthermore, Stein et al (2008) have shown that P. indica -induced resistance against powdery mildew requires jasmonic acid (JA), but no salicylic acid (SA) in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…S3 A, B, and D, Table S2, and SI Materials and Methods) identified UCN as At1g51170 (Fig. 3A), encoding a member of the plant-specific AGC VIII family of protein kinases (22)(23)(24)(25). UCN is a functional kinase that can autophosphorylate in trans as well as transphosphorylate the general kinase substrate myelin basic protein (Fig.…”
Section: Ucn Restrains Growth In Various Lateral Organs and The Embryomentioning
confidence: 99%